A Detailed Comparative Analysis of Anterior Versus Posterior Approach to Lenke 5C Curves. Issue 5 (1st March 2018) - Miyanji, Firoz; Nasto, Luigi A.; Bastrom, Tracey; Samdani, Amer F.; Yaszay, Burt; Clements, David; Shah, Suken A.; Lonner, Baron; Betz, Randal R.; Shufflebarger, Harry L.; Newton, Peter O.
Abstract : Study Design: Prospective cohort study. Objective: To prospectively compare radiographic, perioperative, and functional outcomes between anterior spinal instrumentation and fusion (ASIF) and posterior spinal instrumentation and fusion (PSIF) in Lenke 5C curves. Summary of Background Data: Historically, ASIF has been the treatment of choice for treatment of thoracolumbar adolescent idiopathic scoliosis. More recently, PSIF has gained popularity for its ease, versatility, and amount of correction achieved. Current literature lacks a prospective comparative analysis between these two approaches to better aid treating surgeons in decision making when treating Lenke 5C curves. Methods: A prospective, longitudinal multicenter adolescent idiopathic scoliosis database was used to identify 161 consecutive patients with Lenke 5C curves treated by ASIF with a dual rod system, or PSIF with a pedicle screw-rod construct. Pre- and 2-year postoperative radiographic data, Scoliosis Research Society outcome scores, and perioperative comparisons were made between the two approaches. Results: A total of 69 patients were treated with ASIF and 92 patients with PSIF. Curve extent, magnitude, stable, and end vertebrae distribution before surgery were similar between the two groups. At 2-year follow-up, there were no significant differences in percentage correction of the main curve (ASIF: 59.1%, PSIF: 59.6%), C7 decompensation (ASIF: −0.6 ± 1.2, PSIF: −0.3 ± 1.4 cm), length of hospital stay (ASIF: 5.6 days, PSIF: 5.7 days), postoperative day conversion to oral pain medication (ASIF: 3.2 days, PSIF: 3.2 days), and SRS outcome scores ( P  = 0.560) between the two groups. The number of levels fused was significantly lower in ASIF group (ASIF: 4.7, PSIF: 6.3; P  < 0.001), but PSIF resulted in significantly less disc angulation below lowest instrumented vertebrae (ASIF: 3.4°, PSIF: 1.7°; P  = 0.011), greater lumbar lordosis ( P  < 0.001), and greater % correction of lumbar prominence ( P  = 0.017). Conclusion: The amount of correction achieved was similar between ASIF and PSIF. ASIF resulted in shorter fusions (average 1.6 levels) compared with PSIF. This was at the expense of increased disc angulation below the lowest instrumented vertebrae, less lumbar lordosis, and a lower % correction of the lumbar prominence than PSIF. Level of Evidence: 2